1988
DOI: 10.1210/mend-2-11-1145
|View full text |Cite
|
Sign up to set email alerts
|

SEQUENCES OF INTEREST: Homologous Sequences in Steroidogenic Enzymes, Steroid Receptors and a Steroid Binding Protein Suggest a Consensus Steroid-Binding Sequence

Abstract: The amino acid sequences of two steroidogenic enzymes, P450c17 (steroid 17 alpha-hydroxylase/17,20 lyse) and P450c21 (steroid 21-hydroxylase), are only 28.9% identical. However, these proteins share a region of 21 amino acids bearing 17 identical residues, which we previously suggested may represent the steroid binding site. We assembled a sequence database of known steroid-binding proteins and searched this with the sequence of this 21 amino acid region. The steroidogenic enzymes, P450c17, P450c21, P450scc (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…As the rat is the most widely used experimental animal for studying steroidogenesis, we wished to determine if the rat expressed P450c21 mRNA outside the adrenal. Rat P450c21 cDNA has not been cloned, but our demonstration of a highly conserved putative steroid-binding site, in addition to the known species conservation of the heme-binding site in steroidogenic P450s (20), suggested that some regions of the rat and human P450c21 sequences would be sufficiently similar (i.e., nearly identical) to yield hybrids resistant to RNase A. In the absence of a known rat P450c21 sequence, the number, length, and location of the regions of high similarity between rat and human P450c21 could not be determined.…”
Section: Resultsmentioning
confidence: 89%
“…As the rat is the most widely used experimental animal for studying steroidogenesis, we wished to determine if the rat expressed P450c21 mRNA outside the adrenal. Rat P450c21 cDNA has not been cloned, but our demonstration of a highly conserved putative steroid-binding site, in addition to the known species conservation of the heme-binding site in steroidogenic P450s (20), suggested that some regions of the rat and human P450c21 sequences would be sufficiently similar (i.e., nearly identical) to yield hybrids resistant to RNase A. In the absence of a known rat P450c21 sequence, the number, length, and location of the regions of high similarity between rat and human P450c21 could not be determined.…”
Section: Resultsmentioning
confidence: 89%
“…These include a gene on the opposite strand of the gene for rat gonadotropin-releasing hormone (23), two Drosophila loci (24,25), a mouse locus of unknown function (26), and a newly described member of the c-erbA gene family on the opposite strand from the gene encoding a rat (27) and human (28) and the transcript from its opposite strand is unknown, it is obviously of interest that both mRNAs are found in the adrenal, suggesting a role in steroidogenesis. Potential roles in cholesterol transport or as a trans-acting regulatory protein cannot be evaluated at present, but the opposite-strand transcript we have described probably cannot encode another steroidogenic enzyme, as the genes for these are largely known (2), the available protein sequence lacks a steroid binding site (29), and only deficiency of 21-hydroxylase is linked to HLA (1, 2). P450c21 and the mRNA encoding the 2.7-kb cDNA are both found in the adrenal, but we do not know whether they are expressed in the same cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the steroidbinding ability of PSBP, UG/CC10 and msABP [9,10,12,35] might be relevant, if it is demonstrated for the FHG22 protein. However, no homologies have been found to the canonical (but not general) steroid-binding sequence motif [42] in any of these proteins, while it has been found that besides steroids and polychlorinated biphenyls, rabbit UG binds retinoids and probably membrane proteins [21,43] and human CC10 binds calcium [20]. The protein might be secreted both to the saliva and eye secretion and bind different ligands, playing a role similar to the immunomodulatory/protective action described for UG/CC10 in the female genital tract [10,44] and the lungs [31,32].…”
Section: Tissue-specific Expression Of the Fhg22 Mrnamentioning
confidence: 99%